Factores de riesgo asociados a hipotermia neonatal en la unidad de neonatología del Hospital Regional Docente de Trujillo 2005 - 2015 - De Gracia Dionicio, Christian José (2018)
Neonatal hypothermia is an important cause of morbidity and mortality in developing countries. OBJECTIVE: To assess if prematurity, low birth weight, low apgar and cesarean section are factors associated with the risk of neonatal hypothermia in the Neonatology Unit of the Regional Teaching Hospital of Trujillo during the years 2005-2015. MATERIALS AND METHODS: Case and control study. The sample consisted of 77 cases (neonates with hypothermia) and 154 controls (neonates with temperature in normal ranges). To determine if there are statistically significant differences, the Chi square test was used. To estimate the risk, the Odds Ratio (OR) with a 95% confidence interval (CI) was used. RESULTS: In the bivariate analysis significant differences were found (p<0.05) with the variables prematurity, low birth weight and cesarean section with an OR of 6.8 (CI: 3.596 - 13.150), 4.2 (CI: 2,219 - 8,242) and 2.3 (CI: 1,366 - 4,181) respectively. CONCLUSION: Prematurity, low birth weight and cesarean section are factors associated with the risk of Neonatal Hypothermia